Grey Economy and Perspectives of Bulgarian Businesses Development in the EU Accession Period - Goev, Valentin; Boshnakov, Venelin (Ekonomika, 2008)
he paper suggests some empirical evidence on selected issues related to the influence of business environment factors and corruption practices anticipated as barriers to the successful finalization of the transformation of Bulgarian economy and its integration in the common European economic space. The analysis utilizes sample data from a questionnaire survey among 345 representatives of business organizations having ownership, managerial, or expert positions within the firm. During the survey, respondents expressed their opinions about the spread of grey economy as well as about various aspects of transactions underreporting practices in their branch, providing a ground for the evaluation of the impact of these phenomena on the perceived potential for private businesses development. Evidence from business people attitudes is provided in support of the opinion that restraining the corruption and bureaucratic barriers, provision of the higher public decision-making transparency, as well as improving law enforcement and judiciary system effectiveness are important conditions for domestic entrepreneurship stimulation and overall stable economic growth within the European economy.